Myocardial ischemia/reperfusion upregulates the transcription of the Neuregulin1 receptor ErbB3, but only postconditioning preserves protein translation: Role in oxidative stress. (15th April 2017) - Morano, Michela; Angotti, Carmelina; Tullio, Francesca; Gambarotta, Giovanna; Penna, Claudia; Pagliaro, Pasquale; Geuna, Stefano
Abstract: Background: Neuregulin1 (Nrg1) and its receptors ErbB are crucial for heart development and for adult heart structural maintenance and function and Nrg1 has been proposed for heart failure treatment. Infarct size is the major determinant of heart failure and the mechanism of action and the role of each ErbB receptor remain obscure, especially in the post-ischemic myocardium. We hypothesized that Nrg1 and ErbB are affected at transcriptional level early after ischemia/reperfusion (I/R) injury, and that the protective postconditioning procedure (PostC, brief cycles of ischemia/reperfusion carried out after a sustained ischemia) can influence this pathway. Methods and results: The Langendorff's heart was used as an ex-vivo model to mimic an I/R injury in the whole rat heart; after 30 min of ischemia and 2 h of reperfusion, with or without PostC, Nrg1 and ErbB expression were analysed by quantitative real-time PCR and Western blot. While no changes occur for ErbB2, ErbB4 and Nrg1, an increase of ErbB3 expression occurs after I/R injury, with and without PostC. However, I/R reduces ErbB3 protein, whereas PostC preserves it. An in vitro analysis with H9c2 cells exposed to redox-stress indicated that the transient over-expression of ErbB3 alone is able to increase cell survival (MTT assay), limiting mitochondrial dysfunction (JC-1 probe) and apoptotic signals (Bax/Bcl-2 ratio). Conclusions: This study suggests ErbB3 as a protective factor against death pathways activated by redox stress and supports an involvement of this receptor in the pro-survival responses.